1992
DOI: 10.1111/j.1365-2249.1992.tb06470.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha and dexamethasone inhibit adhesion of T cells to endothelial cells and synovial cells

Abstract: We investigated whether interferon-gamma (IFN-gamma), interferon-alpha (IFN-alpha) and glucocorticoids affected the adhesion of T cells to human umbilical endothelial cells or human synovial cells. About 30% of peripheral blood T cells could bind to unstimulated endothelial cells, but only a few T cells could bind to unstimulated synovial cells. When both endothelial cells and synovial cells were cultured with recombinant IFN-gamma (rIFN-gamma), the percentage of T cell binding to both types of cells increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Corticosteroids have been reported to inhibit expression of several leukocyte adhesion molecules on endothelial cells, thereby reducing leukocyte adherence (17, 20–22). Additionally, corticosteroids are known to exert a significant antiangiogenic effect (23, 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids have been reported to inhibit expression of several leukocyte adhesion molecules on endothelial cells, thereby reducing leukocyte adherence (17, 20–22). Additionally, corticosteroids are known to exert a significant antiangiogenic effect (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are known to be potent inflammation inhibitors that down‐regulate the expression of cellular adhesion molecules, cytokines, and growth factors on endothelial cells (15–18) in an NF‐κB–dependent manner (16, 19), with decreased adhesion of immune cells as a consequence (20–22). Additionally, they exert significant antiangiogenic effects (23, 24).…”
mentioning
confidence: 99%
“…Although the milder rise of circulating TNF level could account for the prevention of up-regulation of ICAM-1 expression in IFN-␣-treated infected mice, this was in conflict with the highly increased levels of IFN-␥. However, Eguchi et al (39) have shown that IFN-␣ is able to downregulate ICAM-1 expression even on IFN-␥-stimulated endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…6. adhesion after endothelium treatment with Dx in vitro (10). We investigated the binding of PBMNCs from MP-treated MS patients to endothelium, analysing the effects of the drug on lympho-monocytes and their adhesion molecules.…”
Section: Resultsmentioning
confidence: 99%